Association of Polo-Like Kinase 3 and PhosphoT273 Caspase 8 Levels With Disease-Related Outcomes Among Cervical Squamous Cell Carcinoma Patients Treated With Chemoradiation and Brachytherapy - Fleischmann, Max; Martin, Daniel; Peña-Llopis, Samuel; Oppermann, Julius; von der Grün, Jens; Diefenhardt, Markus; Chatzikonstantinou, Georgios; Fokas, Emmanouil; Rödel, Claus; Strebhardt, Klaus; Becker, Sven; Rödel, Franz; et al. (Frontiers in Oncology, 2019)
Introduction: Definitive chemoradiotherapy (CRT) followed by high-dose-rate (HDR) brachytherapy (BT) is the state-of-the-art treatment for locally advanced (≥ FIGO IIb) cervical cancer but three-year survival rates are stagnating in recent years indicating the need for biomarker development and patient’s stratification. In the present study we aimed to analyse the predictive relevance of Polo-like kinase (PLK) 3 expression and levels of Caspase 8 T273 phosphorylation in patients with advanced cervical squamous cell carcinoma (CSCC) treated with CRT and BT. Methods: In a cohort of 74 patients with FIGO Stage Ib to IVb cervix carcinoma baseline immunohistochemical scoring of PLK3, pT273 Capsase 8 was performed on pre- treatment biopsies and correlated with clinical/histopathological characteristics including p16INK4a expression. Marker expression was further correlated to clinical endpoints cumulative incidence of local and distant failure, cancer specific (CSS), and overall survival (OS) and validated using the Cancer Genome Atlas (TCGA) dataset. Results: We observed significant correlations between PLK3 expression, pT273 caspase 8 detection (p=0.009), N stage (p=0.046), M-stage (p=0.026) and FIGO category (p=0.001), while pT273 Caspase 8 was significantly associated with T-stage (p=0.031). A high score of PLK3 was associated with a lower incidence of distant failure (p=0.011), increased CSS (p=0.001) and more favorable OS (p=0.009) in univariate analyses. Further, pT273 Caspase 8 phosphorylation was associated with a decreased distant failure (p=0.021) and increased CSS (p<0.001) and OS (p<0.001) in univariate and remained significant for OS in multivariate analyses. Using TCGA data, we confirmed the association of low PLK3 expression with resistance to radiotherapy and brachytherapy (p<0.05), as well as increased propensity for metastases (p=0.004). Finally, a combined PLK3 and pT273 Caspase 8 variable predicted for decreased distant failure (p=0.005), increased CSS (p<0.001) and OS (p<0.001) and remained significant for distant failure (p=0.041) and CSS (p=0.003) in multivariate analyses. Conclusion: These data indicate that elevated levels of PLK3 and pT273 Caspase 8 are correlated with a favorable clinical outcome in patients with cervical carcinoma treated with definitive CRT and BT.